PENGARUH BRAND IMAGE DAN BRAND TRUST TERHADAP BRAND LOYALTY PADA PENGGUNA TELKOMSEL (Studi pada Mahasiswa Universitas Riau) - Gunva, Bagus Abyan Hafizh; Fadli, Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the effect of brand image and brand trust on brand loyalty among Telkomsel users, specifically undergraduate students at the University of Riau. The research background is based on the intense competition within Indonesia’s telecommunications industry, where despite Telkomsel’s market leadership, its relatively high pricing has led some customers to switch to competitors. This research employs a quantitative method with a descriptive and verificative approach. Primary data were collected through questionnaires distributed to 100 respondents selected using a purposive sampling technique. Data analysis was conducted using multiple linear regression, t-tests, F-tests, and the coefficient of determination with SPSS 26. The results reveal that (1) brand image has a positive and significant effect on brand loyalty, (2) brand trust has a positive and significant effect on brand loyalty, and (3) brand image and brand trust simultaneously have a positive and significant effect on brand loyalty. These findings indicate that a strong brand image and high brand trust can enhance customer loyalty. Keywords: Brand Image, Brand Trust, Brand Loyalty, Telkomsel, Students.